Transformational Leadership Style And Human Resource Management Challenges In The Society 5.0 Era - Reis Alta Peggi; Havis Aravik (Penerbit dan Percetakan CV.Picmotiv, 2025)
The Society 5.0 era is characterized by the integration of advanced technologies such as artificial intelligence, the Internet of Things, and big data into various aspects of life and the workplace. This situation brings significant challenges for human resource management, particularly in maintaining a balance between the use of technology and human values. This article aims to analyze the role of transformational leadership in addressing human resource management challenges in the Society 5.0 era. The research method used is a qualitative approach with a literature study, reviewing various journal articles, reference books, and relevant scientific publications from the past five years. The study results show that transformational leadership plays an important role in enhancing employee motivation, commitment, and performance, while also serving as a bridge between technological advancement and humanistic values within organizations. This leadership style can drive digital adaptation, competency development, as well as the creation of an innovative and ethical work culture. Thus, the implementation of transformational leadership becomes a relevant and effective strategy for organizations to enhance competitiveness and sustainability in the era of Society 5.0.